PENGENALAN PERANAN PERBANKAN SYARIAH BAGI PEREKONOMIAN MASYARAKAT DI DESA PURASEDA, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Farhan Zaini Tamam; Tubagus Rifqy Thantawi; Azizah Mursyidah (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract The national economy depends on the economic movement of people. As a result of regulations restricting community mobility, the COVID 19 pandemic has changed lifestyles to accelerate economic activities. In the third quarter of 2020, Indonesia even formally entered into a recession with -3,49% economic growth. Also affected was the Islamic banking industry, which is one of the financial intermediary institutions, but not worse than conventional banking. This article seeks to determine the state's role in Islamic banking resilience during the COVID-19 pandemic. Keyword: Islmic Banking Industy, People’s Economy, Covid-19